Annual Plan 1997-98 Volume-I An Overview Government of Assam - Planning Commission (Planning Commission, 1997)
Assam, Comprising Of Two Distinct Natural Divisions, 23 Districts, 48 Sub-Divisions, 149 Revenue Circles And 217 Development Blocks, With An Area Of About 78,438 Sq. Kms, Forms The Core Of The North-Eastern Region. Its Two Distinct Natural Divisions-The Plains Cover The Plains Cover An Area Of 63,116 Sq. Kms And Accounts For About 80.5 Percent Of The Total Land Surface Of The State, While The Hills Cover An Area Of 15,322 Sq. Kms And Accounts For About 19.5 Percent Of The Total Land Area. The Share Of The State In The Country's Geographical Area Is Only 2.4 Percent And Its Share In Population Is Around 2.6 Percent.
Planning and Development Department
Government of Assam Planning and Development Department